2014
DOI: 10.1038/bmt.2013.204
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vivo T-cell depletion on outcome of AML patients in first CR given peripheral blood stem cells and reduced-intensity conditioning allo-SCT from a HLA-identical sibling donor: a report from the Acute Leukemia Working Party of the European group for Blood and Marrow Transplantation

Abstract: The impact of in vivo T-cell depletion on transplantation outcomes in patients transplanted with reduced-intensity conditioning (RIC) remains controversial. This study assessed the outcome of 1250 adult patients with de novo AML in first CR (CR1) given PBSC from HLA-identical siblings after chemotherapy-based RIC. A total of 554 patients did not receive any form of in vivo T-cell depletion (control group), whereas antithymocyte globulin (ATG) and alemtuzumab were given in 444 and 252 patients, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
81
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 41 publications
15
81
5
1
Order By: Relevance
“…Other retrospective studies comparing RIC with MAC in AML have shown similar DFS and OS as in our analysis, but the increased relapse incidence usually associated with RIC was not found in the present report [16,30]. We also found that in-vivo T-cell depletion with ATG was not associated with an increased risk of relapse as it has been recently described [31].…”
Section: Discussionsupporting
confidence: 78%
“…Other retrospective studies comparing RIC with MAC in AML have shown similar DFS and OS as in our analysis, but the increased relapse incidence usually associated with RIC was not found in the present report [16,30]. We also found that in-vivo T-cell depletion with ATG was not associated with an increased risk of relapse as it has been recently described [31].…”
Section: Discussionsupporting
confidence: 78%
“…11 In contrast, a similar recent EBMT study failed to detect either association. 12 Because transplant outcomes are also dependent on recipient age, type of donor, disease risk and status at transplant, 22,23 in order to evaluate the impact of GVHD prophylaxis on transplant outcomes more accurately, in the present study we limited the analysis to a very homo-GVHD prophylaxis in RIC HSCT haematologica | 2015; 100 (5) 687 Table 3. Transplant outcomes at 2 years after allogeneic hematopoietic stem cell transplantation according to the GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of graft-versus-host disease prophylaxis in reduced-intensity conditioning allogeneic stem cell transplant in acute myeloid leukemia: a study from the Acute Leukemia Working Party of the European Group for Blood and Marrow Transplantation Marie Thérèse Rubio, 1,2,3 Myriam Labopin, 1,4 Didier Blaise, 5 Gerard Socié, 6 Rafael Rojas Contreras, 7 Patrice Chevallier, 8 Miguel A. Sanz, 9 Stéphane Vigouroux, 10 Anne Huynh, 11 Avichai Shimoni, 12 Claude-Eric Bulabois, 13 Nerea Caminos, 14 Lucía López-Corral, 15 Arnon Nagler, 12,4 * and Mohamad Mohty 1,2,3,4 * been poorly explored. While, the combination of CsA and a short course of methotrexate (MTX) after transplantation is considered as the gold standard for GVHD prophylaxis after conventional myeloablative allogeneic HSCT from HLA-identical siblings, 15,16 there is no consensus on the optimal preventive regimen for GVHD prophylaxis after RIC allogeneic HSCT.…”
Section: ©2015 Ferrata Storti Foundation This Is An Open-access Papementioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are in accordance with earlier report by other smaller studies, [21][22][23] as well as to a recent publication by our group on 1250 adult patients with de novo AML in CR1 given PBSC from HLA-identical siblings after chemotherapy-based RIC regimen, where the use of ATG and the use of alemtuzumab were each associated with a lower risk of chronic GVHD, but a similar risk of relapse. 24 Because of the selection criteria (only patients 8/8 matched were considered), we were unable to assess the impact of mismatches on the risk of chronic GvHD and eventually NRM. Moreover, the type and dose of ATG were unknown for a sizeable number of the patients in our study.…”
Section: Discussionmentioning
confidence: 99%